A kind of white biodegradable plastic coated wire and preparation method thereof

By wrapping white biodegradable plastic-clad wire on the metal wire, the problems of oxidative corrosion and inconvenience in use of metal wire are solved, better protection effect and a wider scope of application are achieved, and it meets environmental protection requirements.

CN118692734BActive Publication Date: 2025-03-04JIANGYIN KEYU METAL PROD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410919187.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-05-16
Filing Date
2024-07-09
Publication Date
2025-03-04
Estimated Expiration
2044-07-09

AI Technical Summary

Technical Problem

Common metal wires are prone to oxidation and corrosion during use, and are not easy to fit with the plastic wrap layer, resulting in separation and affecting the use effect. At the same time, the ends of the metal wire may cause harm to the human body, especially those who are allergic to metals.

Method used

A white degradable plastic wrap wire is used, which consists of the metal wire, the wrap layer and the chelating layer in the middle. The plastic-inclusion layer consists of degradable plastic particles, titanium dioxide, antistatic agents, weatherproofing agents, etc. The chelating layer is composed of metal corrosion agents, metal chelating agents, etc. The plastic-inclusion layer is evenly wrapped on the metal wire through spraying and extruder technology.

Benefits of technology

It effectively prevents oxidation and corrosion of metal wires, enhances the fit between the plastic wrap layer and the metal wire, extends the service life, and is suitable for people with metal allergies. At the same time, the plastic wrap layer can degrade after use, meeting environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118692734B_ABST
    Figure CN118692734B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of plastic-coated wires, and discloses a white degradable plastic-coated wire and a preparation method thereof, wherein the plastic-coated wire is composed of a metal wire in the middle, a plastic-coated layer included on the outer side of the metal wire, and a chelating layer that integrates the plastic-coated layer with the metal wire. The plastic-coated layer is composed of the following components by weight: 60-99.8 parts of degradable plastic particles, 3-30 parts of titanium dioxide, 1-2 parts of antistatic agents, 1-2 parts of anti-weathering agents, 0-2 parts of plastic production aids, and 0-8 parts of plastic functional aids. The chelating layer is composed of the following components by weight: 0.5-1 parts of metal corrosive agents, 1-2 parts of metal chelating agents, and 0-1 parts of metal rust inhibitors. The plastic-coated layer of the plastic-coated wire can be degraded after use, which is in line with the concept of environmental protection of plastic degradation in modern society. In addition, the structure and preparation process of the white degradable plastic-coated wire are simple and scientific, and the quality of the prepared plastic-coated wire is uniform and stable, which is suitable for promotion and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic-coated wires, and more specifically discloses a white biodegradable plastic-coated wire and a preparation method thereof. Background Art

[0002] Metal wire is made of metal wire rods, coils or metal bars as raw materials, and is processed through professional equipment such as wire drawing equipment and annealing equipment. After multiple drawing, annealing, re-drawing, re-annealing and other processes, it is processed into various filamentary or linear products of different specifications and models. This product is called metal wire. The use of metal wire is very common. It can be used to bundle materials, folded into various pendants, and can also be prepared into various buckles. Common metal wires are exposed to the air as a whole, and will oxidize in contact with the space, causing the metal wire to oxidize and rust, and the metal wire loses its original luster. At the same time, because the metal wire and the plastic coating cannot be effectively bonded, the plastic coating and the metal wire are prone to separation, affecting its use effect. In addition, if the metal wire and the workpiece prepared by it come into direct contact with the human skin during use, the end of the metal wire will cause harm to the user, especially for people who are allergic to metals, who cannot come into direct contact with metal wire products at all, affecting the scope of use of metal wire products. Summary of the invention

[0003] The present invention mainly provides a white biodegradable plastic-coated wire and a preparation method thereof, which can solve the problems that common metal wires are not well protected and are prone to oxidation and rust and are not applicable to a wide range of people.

[0004] To solve the above technical problems, according to one aspect of the present invention, more specifically, a white biodegradable plastic coated wire is provided, which comprises a metal wire in the middle, a plastic coating layer on the outer side of the metal wire, and a chelating layer that integrates the plastic coating layer and the metal wire.

[0005] The plastic coating layer is composed of the following components in parts by weight: 60-99.8 parts of degradable plastic particles, 3-30 parts of titanium dioxide, 1-2 parts of antistatic agent, 1-2 parts of anti-weathering agent, 0-2 parts of plastic production additives and 0-8 parts of plastic functional additives.

[0006] The chelating layer is composed of the following components in parts by weight: 0.5-1 part of metal corrosive agent, 1-2 parts of metal chelating agent and 0-1 part of metal rust preventive agent.

[0007] Furthermore, the metal wire includes iron wire, steel wire, galvanized iron wire and galvanized steel wire.

[0008] Furthermore, the degradable plastic particles are one of polylactic acid PLA particles, poly 3-hydroxyalkanoate PHA particles, polybutylene adipate / terephthalate PBAT particles or polybutylene succinate PBS particles, or a mixture of the two;

[0009] The chelating agent is one or more of ethylenediaminetetraacetic acid, bidentate 2,2'-bipyridine, bidentate 1,10-phenanthroline, methylbenzotriazole or mercaptobenzotriazole;

[0010] The antistatic agent is any one of bis(β-hydroxyethyl)coconut amine, bis(β-hydroxyethyl)stearylamine, coconut alkyl quaternary amine ethoxylate and coconut methyl ammonium chloride;

[0011] The anti-weathering agent is any one of quartz sandstone powder, granite powder or limestone powder;

[0012] The metal corrosive agent is a picric acid / hydrochloric acid ethanol solution, and the metal rust inhibitor is any one of a zinc phosphate / zinc nitrate / lead carbonate aqueous solution, a dihydrogen manganese ferric phosphate / zinc nitrate / manganese nitrate aqueous solution, a dihydrogen manganese ferric phosphate / zinc nitrate aqueous solution, or a dihydrogen manganese ferric phosphate / zinc nitrate / phosphoric acid / sodium nitrate aqueous solution;

[0013] The plastic production aid is a lubricant pentaerythritol stearate PETS;

[0014] The plastic functional additive is any one of the main antioxidants 2,6-di-tert-butylphenol, diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)]propionate or 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, accounting for 50%, and any one of the auxiliary antioxidants pentaerythritol diphosphite diisobutyl ester, tributyl phosphite, tri(2,4-di-tert-butylphenyl) phosphite, pentaerythritol diphosphite distearyl ester or bis(2,4-di-tert-butylphenyl) pentaerythritol bis diphosphite, accounting for 50%.

[0015] Furthermore, the thickness of the plastic coating layer is 0.02-2 mm.

[0016] Furthermore, the cross-sectional area of ​​the metal wire is 0.05-100 square millimeters.

[0017] Furthermore, the cross-section of the plastic-coated wire may be circular, elliptical, triangular, C-shaped, diamond-shaped or trapezoidal.

[0018] According to another aspect of the present invention, there is provided a method for preparing a degradable plastic-coated wire, comprising the following steps:

[0019] S1. 60-95 parts of degradable plastic particles, 3-30 parts of titanium dioxide, 1-2 parts of antistatic agent, 1-2 parts of anti-weathering agent, 0-2 parts of plastic production additives and 0-8 parts of plastic functional additives are uniformly mixed to prepare a plastic coating layer raw material;

[0020] S2, spray a layer of metal corrosive agent on the metal wire for 30 minutes, rinse the surface of the metal wire with water, soak it in a metal rust inhibitor for 10-15 minutes, take out the surface moisture at 50°C and vacuum dry it, spray the ethanol solution of the chelating agent while it is hot, blow dry it with hot air, and obtain a metal wire with a chelating layer attached;

[0021] S3, adding the plastic coating material prepared in step S1 into the extruder, setting the temperature of the extruder to 80-200 degrees Celsius, and passing the metal wire through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with the plastic coating layer formed by the molten plastic coating material;

[0022] S4, sending the metal wire wrapped with the plastic coating layer into water at 5-35 degrees Celsius for cooling and winding to complete the preparation of the degradable plastic coated wire.

[0023] Furthermore, during the preparation of the degradable plastic-coated wire, the metal wire advances at a speed of 50-300 meters.

[0024] The beneficial effects of the white degradable plastic coated wire and the preparation method thereof of the present invention are as follows: the metal wire is corroded by the rusting agent, and rust pits appear on the surface, so that the contact area and friction coefficient between the metal wire and the plastic coating layer are increased, and the mutual interlocking points between the plastic coating layer and the metal wire are increased. The outer side of the metal wire is evenly wrapped with a metal complexing agent, so that the plastic coating layer and the metal wire are complexed into one, so that the plastic coating layer and the metal wire are tightly fitted, and it is not easy for the plastic coating layer and the metal wire to separate; wrapped with a metal rust inhibitor, it can effectively prevent metal oxidation and rust, and increase the usable range of the plastic coating wire, and can extend the service life of the plastic coating wire; in the process of use, it has various properties of the metal wire, and due to the presence of the plastic coating layer, the metal wire is effectively protected, so that the metal wire can keep its own metallic luster for a long time, and the broken section is passivated; it is more suitable for users with metal allergies; the plastic coating layer of the plastic coating wire can be degraded after use, which is in line with the modern society's concept of plastic degradation and environmental protection. In addition, the structure and preparation process of the white degradable plastic coated wire are simple and scientific, and the quality of the prepared plastic coated wire is uniform and stable, which is suitable for promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0026] Figure 1 It is a schematic diagram of the structure of the plastic-coated wire.

[0027] In the figure: 1. Metal wire; 2. Plastic coating layer; 3. Chelating layer. DETAILED DESCRIPTION

[0028] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0029] Embodiment 1

[0030] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0031] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover on a round iron wire with a cross-sectional area of ​​3 mm2 and rinse with clean water after 30 min.

[0032] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round iron wire in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0033] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0034] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0035] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0036] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 120 meters.

[0037] Embodiment 2

[0038] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0039] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal corrosion agent. Spray the metal corrosion agent on a round steel wire with a cross-sectional area of ​​30 mm2 and rinse with clean water after 30 min.

[0040] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round steel wire in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0041] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0042] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 2 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0043] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0044] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 150 meters.

[0045] Embodiment 3

[0046] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0047] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover onto a round galvanized iron wire with a cross-sectional area of ​​60 mm2 and rinse with clean water after 30 min.

[0048] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round galvanized iron wire in step (2) in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0049] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0050] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 0.5 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0051] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0052] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 200 meters.

[0053] Embodiment 4

[0054] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0055] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal corrosion agent. Spray the metal corrosion agent on an oval galvanized steel wire with a cross-sectional area of ​​90 mm2 and rinse with clean water after 30 min.

[0056] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the oval galvanized steel wire in step (2) in the hot solution after dissolution for 15 min, take out and dry in vacuum at 50 ° C;

[0057] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0058] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0059] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0060] During the preparation process of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 180 meters.

[0061] Embodiment 5

[0062] (1) adding 900 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0063] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover on a diamond-shaped iron wire with a cross-sectional area of ​​100 mm2 and rinse with clean water after 30 min.

[0064] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the diamond iron wire in step (2) in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0065] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0066] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 2 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0067] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0068] During the preparation process of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 180 meters.

[0069] Embodiment 6

[0070] (1) adding 900 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0071] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover on a round galvanized steel wire with a cross-sectional area of ​​60 mm2 and rinse with clean water after 30 min.

[0072] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round galvanized steel wire in step (2) in the hot solution after dissolution for 15 min, take out and dry in vacuum at 50 ° C;

[0073] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0074] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0075] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0076] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 60 meters.

[0077] Embodiment 7

[0078] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0079] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal corrosion agent. Spray the metal corrosion agent on a round steel wire with a cross-sectional area of ​​0.05 mm2 and rinse with clean water after 30 min.

[0080] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round steel wire in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0081] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0082] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a plastic coating layer formed by the molten plastic coating raw material with a thickness of 0.02 mm;

[0083] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0084] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 50 meters.

[0085] Embodiment 8

[0086] (1) adding 700 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0087] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover on a C-shaped galvanized steel wire with a cross-sectional area of ​​60 mm2 and rinse with clean water after 30 min.

[0088] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the C-shaped galvanized steel wire in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0089] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0090] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0091] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0092] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 200 meters.

[0093] Embodiment 9

[0094] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0095] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal corrosion agent. Spray the metal corrosion agent onto a round galvanized iron wire and a galvanized steel wire with a cross-sectional area of ​​100 mm2, and rinse with clean water after 30 min.

[0096] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, put the round galvanized iron wire and galvanized steel wire in step (2) into the hot solution after dissolution and soak for 15 min, take out and dry in a vacuum at 50 ° C;

[0097] (4) spraying the dried iron wire obtained in step (3) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0098] (5) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (4) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 2 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0099] (6) The metal wire wrapped with the plastic coating layer is placed in water at 20° C. for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0100] Comparative Example 1

[0101] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0102] (2) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 °C and stir to dissolve, place a round iron wire with a cross-sectional area of ​​3 mm2 into the hot solution and soak for 15 min, then take out and dry in a vacuum at 50 °C;

[0103] (3) spraying the dried iron wire obtained in step (2) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0104] (4) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0105] (5) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the degradable plastic coated wire.

[0106] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 120 meters.

[0107] Comparative Example 2

[0108] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0109] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover on a round iron wire with a cross-sectional area of ​​3 mm2 and rinse with clean water after 30 min.

[0110] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round iron wire in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0111] (4) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0112] (5) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the degradable plastic coated wire.

[0113] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 120 meters.

[0114] Comparative Example 3

[0115] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0116] (2) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 °C and stir to dissolve, place a round iron wire with a cross-sectional area of ​​3 mm2 into the hot solution and soak for 15 min, then take out and dry in a vacuum at 50 °C;

[0117] (3) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 1 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0118] (4) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0119] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 120 meters.

[0120] Comparative Example 4

[0121] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0122] (2) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 °C and stir to dissolve, place a round steel wire with a cross-sectional area of ​​30 mm2 into the hot solution and soak for 15 min, then take out and dry in a vacuum at 50 °C;

[0123] (3) spraying the dried iron wire obtained in step (2) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0124] (4) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 2 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0125] (5) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the degradable plastic coated wire.

[0126] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 150 meters.

[0127] Comparative Example 5

[0128] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0129] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal corrosion agent. Spray the metal corrosion agent on a round steel wire with a cross-sectional area of ​​30 mm2 and rinse with clean water after 30 min.

[0130] (3) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 ° C and stir to dissolve, soak the round steel wire in the hot solution after dissolution for 15 min, take out and dry in a vacuum at 50 ° C;

[0131] (4) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 2 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0132] (5) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the degradable plastic coated wire.

[0133] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 150 meters.

[0134] Comparative Example 6

[0135] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0136] (2) Add 14 g zinc phosphate, 28 g zinc nitrate, 0.05 g lead carbonate and 2000 L water into a 5 L beaker, heat to 65 °C and stir to dissolve, place a round steel wire with a cross-sectional area of ​​30 mm2 into the hot solution and soak for 15 min, then take out and dry in a vacuum at 50 °C;

[0137] (3) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., passing the metal wire obtained in step (2) through the discharge port of the extruder, so that the outer side of the metal wire is evenly coated with a 2 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0138] (4) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0139] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 150 meters.

[0140] Comparative Example 7

[0141] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0142] (2) Add 14g zinc phosphate, 28g zinc nitrate, 0.05g lead carbonate and 2000L water into a 5L beaker, heat to 65°C and stir to dissolve, put a round galvanized iron wire with a cross-sectional area of ​​60mm2 into the hot solution after dissolution and soak for 15min, take out and dry in vacuum at 50°C;

[0143] (3) spraying the dried iron wire obtained in step (2) with 200 ml of ethanol solution containing 10 g of bidentate 1,10-phenanthroline while it is still hot, and drying with hot air at 60° C.;

[0144] (4) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 0.5 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0145] (5) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the degradable plastic coated wire.

[0146] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 200 meters.

[0147] Comparative Example 8

[0148] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0149] (2) Add 5 g of picric acid to a 1 L round-bottom flask, add 500 ml of ethanol and stir to dissolve, then add 25 ml of 37% concentrated hydrochloric acid and stir for 5 min to obtain a metal rust remover. Spray the metal rust remover onto a round galvanized iron wire with a cross-sectional area of ​​60 mm2 and rinse with clean water after 30 min.

[0150] (3) Add 14g zinc phosphate, 28g zinc nitrate, 0.05g lead carbonate and 2000L water into a 5L beaker, heat to 65°C and stir to dissolve, put a round galvanized iron wire with a cross-sectional area of ​​60mm2 into the hot solution after dissolution and soak for 15min, take out and dry in vacuum at 50°C;

[0151] (4) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., and passing the metal wire obtained in step (3) through the discharge port of the extruder so that the outer side of the metal wire is evenly coated with a 0.5 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0152] (5) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the degradable plastic coated wire.

[0153] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 200 meters.

[0154] Comparative Example 9

[0155] (1) adding 600 g of poly 3-hydroxyalkanoate particles, 30 g of titanium dioxide, 10 g of bis(β-hydroxyethyl) stearylamine, 10 g of quartz sandstone powder, 10 g of pentaerythritol stearate, 20 g of 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene and 20 g of tri(2,4-di-tert-butylphenyl)phosphite into a pulverizer, pulverizing and mixing to obtain a raw material powder for a plastic coating layer;

[0156] (2) Add 14g zinc phosphate, 28g zinc nitrate, 0.05g lead carbonate and 2000L water into a 5L beaker, heat to 65°C and stir to dissolve, put a round galvanized iron wire with a cross-sectional area of ​​60mm2 into the hot solution after dissolution and soak for 15min, take out and dry in vacuum at 50°C;

[0157] (3) adding the plastic coating raw material powder prepared in step (1) into an extruder, setting the temperature of the extruder to 200° C., passing the metal wire obtained in step (2) through the discharge port of the extruder, so that the outer side of the metal wire is evenly coated with a 0.5 mm thick plastic coating layer formed by the molten plastic coating raw material;

[0158] (4) The metal wire wrapped with the plastic coating layer is placed in 20° C. water for cooling and is rolled up to complete the preparation of the biodegradable plastic coated wire.

[0159] During the preparation of the degradable plastic-coated wire, the metal wire 1 advances at a speed of 200 meters.

[0160] The peel strength tester was used to test the peel strength. The load range of the instrument was 0-500N and the resolution was 0.01N. The results are shown in the following table:

[0161] Table 1 Peel strength test data

[0162] Peel strength (N / m) Embodiment 1 338 Comparative Example 1 256 Comparative Example 2 237 Comparative Example 3 112

[0163] Table 2 Peel strength test data

[0164]

[0165]

[0166] Table 3 Peel strength test data

[0167] Peel strength (N / m) Embodiment 3 455 Comparative Example 7 313 Comparative Example 8 298 Comparative Example 9 155

[0168] It can be seen that the white degradable plastic coated wire prepared by the method of the present invention has a plastic coating evenly wrapped on the outer side of the metal wire, and has various properties of the metal wire during use. Due to the presence of the plastic coating, the metal wire is effectively protected, so that the metal wire retains its own metallic luster for a long time, and the broken section is passivated; it is more suitable for users who are allergic to metals; due to the presence of the chelating agent, the plastic coating layer and the metal wire are chelated into one, and it is not easy for the plastic coating layer and the metal wire to separate during use; because of the presence of the metal rust inhibitor, the application range is wider, and it is not easy to age and rust, and the application time is longer; the plastic coating layer of the plastic coated wire can be degraded after use, which is in line with the modern society's concept of plastic degradation and environmental protection. In addition, the structure and preparation process of the white degradable plastic coated wire are simple and scientific, and the quality of the prepared plastic coated wire is uniform and stable, which is suitable for promotion and use.

[0169] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.

Claims

1. A white biodegradable plastic coated wire, characterized in that: The plastic-coated wire is composed of a metal wire (1) in the middle, a plastic-coated layer (2) on the outer side of the metal wire (1), and a chelating layer (3) that integrates the plastic-coated layer (2) and the metal wire (1); The plastic coating layer (2) is composed of the following components in parts by weight: 60-99.8 parts of degradable plastic particles, 3-30 parts of titanium dioxide, 1-2 parts of antistatic agent, 1-2 parts of anti-weathering agent, 0-2 parts of plastic production additives and 0-8 parts of plastic functional additives; the chelating layer (3) is composed of 0.5-1 parts of metal corrosive agent, 0-1 parts of metal rust inhibitor and 1-2 parts of chelating agent in parts by weight; Wherein, the degradable plastic particles are one of polylactic acid PLA particles, poly 3-hydroxyalkanoate PHA particles, polybutylene adipate / terephthalate PBAT particles or polybutylene succinate PBS particles, or a mixture of the two; The chelating agent is one or more of ethylenediaminetetraacetic acid, bidentate 2,2'-bipyridine, bidentate 1,10-phenanthroline, methylbenzotriazole or mercaptobenzotriazole; The antistatic agent is any one of bis(β-hydroxyethyl)coconut amine, bis(β-hydroxyethyl)stearyl amine, coconut alkyl quaternary amine ethoxylate and coconut methyl ammonium chloride; The anti-weathering agent is any one of quartz sandstone powder, granite powder or limestone powder; The metal corrosive agent is picric acid / hydrochloric acid ethanol solution, and the metal rust inhibitor is any one of zinc phosphate / zinc nitrate / lead carbonate aqueous solution, dihydrogen manganese ferrophosphate / zinc nitrate / manganese nitrate aqueous solution, dihydrogen manganese ferrophosphate / zinc nitrate aqueous solution or dihydrogen manganese ferrophosphate / zinc nitrate / phosphoric acid / sodium nitrate aqueous solution; The plastic production additive is the lubricant pentaerythritol stearate PETS; The plastic functional additive is any one of the main antioxidants 2,6-di-tert-butylphenol, diethylene thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)]propionate or 1,3,5-trimethyl-2,4,6-tri(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, accounting for 50%, and any one of the auxiliary antioxidants diisobutyl dipentaerythritol phosphite, tributyl phosphite, tri(2,4-di-tert-butylphenyl) phosphite, dioctadecyl dipentaerythritol phosphite or bis(2,4-di-tert-butylphenyl) pentaerythritol bis diphosphite, accounting for 50%.

2. The white biodegradable plastic coated wire and the preparation method thereof according to claim 1, characterized in that: The metal wire (1) comprises iron wire, steel wire, galvanized iron wire and galvanized steel wire.

3. The white biodegradable plastic coated wire and the preparation method thereof according to claim 1, characterized in that: The thickness of the plastic coating layer (2) is 0.02-2 mm.

4. The white biodegradable plastic coated wire and the preparation method thereof according to claim 1, characterized in that: The cross-sectional area of ​​the metal wire (1) is 0.05-100 square millimeters.

5. The method for preparing a white biodegradable plastic coated wire according to claim 1, characterized in that: The following steps are involved: S1. 60-99.8 parts of degradable plastic particles, 3-30 parts of titanium dioxide, 1-2 parts of antistatic agent, 1-2 parts of anti-weathering agent, 0-2 parts of plastic production additives and 0-8 parts of plastic functional additives are uniformly mixed to prepare a raw material for the plastic coating layer (2); S2, spraying a layer of metal corrosive agent on the metal wire (1) for 30 minutes, washing the surface of the metal wire with water, soaking it in a metal rust inhibitor for 10-15 minutes, taking it out and drying the surface moisture at 50°C in a vacuum oven, spraying an ethanol solution of a chelating agent while it is still hot, and drying it with hot air to obtain a metal wire (1) with a chelating layer (3) attached thereto; S3, adding the plastic coating layer (2) raw material prepared in step S1 into an extruder, setting the temperature of the extruder to 80-200 degrees Celsius, and passing the metal wire (1) attached with the chelating layer (3) through the discharge port of the extruder, so that the outer side of the metal wire (1) is evenly coated with the plastic coating layer (2) formed by the melted plastic coating layer (2) raw material; S4, sending the metal wire (1) wrapped with the plastic coating layer (2) into water at 5-35 degrees Celsius for cooling and winding to complete the preparation of the biodegradable plastic coated wire.

6. The method for preparing the white biodegradable plastic coated wire according to claim 5, characterized in that: During the preparation of the biodegradable plastic-coated wire, the metal wire (1) advances at a speed of 50-300 meters.

Citation Information

Patent Citations

  • Preparation method of PETG (polyethylene terephthalate glycol) encapsulated wire

    CN103752453A

  • Metal-plastic complex and manufacturing method thereof

    CN104479152A

  • Biodegradable antistatic polylactic acid material and molded product thereof

    CN107541030A

  • Component for tree bonsai modeling

    CN209546381U